Achieving Optimal Safety Inventory Levels for Oil Companies using the CONWIP Approach - Laquanda Leaven; Shengbin Wang; Linda Silver Coley; Silvanus Udoka (International Journal of Supply Chain Management, 2017)
Oil Companies are faced with many operational challenges as it relates to key process functions within their selected manufacturing strategy. These challenges include: high safety stock levels, long lead times, inefficient floor utilization and production planning in regards to bulk/pack raw material receipt, blending, and packaging. The goal of this research study is to address the challenge of high safety stock levels of lubricant products manufactured by oil companies, and to conduct a value stream map (VSM) exercise to frame near term and future state opportunities to optimize cost structures and operational excellence parameters. Based on the analysis of the current VSM for a specified oil company from a lean supply chain perspective, we apply the CONWIP (CONstant Work In Progress) approach to optimize the safety inventory levels, which successfully decreases the costs associated with both raw material and finished goods inventory. In particular, a 3.1 million dollar reduction in finished goods inventory and a 1.4 million dollar reduction in raw material inventory were achieved for a large oil company through implementation of the CONWIP approach. The results of this study indicate this pull-oriented production and inventory control system can certainly benefit additional oil manufacturing companies and help them achieve significant safety inventory cost savings.